Bank Concentration and Stability in Central Asia: The Effect of Capital Regulation and Financial Freedom - Yudaruddin, Rizky (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
In this study, the interrelation between bank concentration and stability is examined, focusing on the joint impact of capital regulation and financial openness. Using the data from the Global Financial Development Database provided by the World Bank and the Index of Financial Freedom from The Heritage Foundation and The Wall Street Journal, a sample of five countries in Central Asia was obtained, specifically during 1993-2017. The results show that the relationship between bank concentration and stability supports the concentration-stability hypothesis. Moreover, higher concentration and well-capitalized banks increase financial stability. However, the effect of bank concentration and financial freedom on stability is negative and significant. Capital regulation and supervision from authority control in the financial sector need to be strengthened to solve financial instability.